2007
DOI: 10.1590/s1413-86702007000200020
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for nosocomial bloodstream infection caused by multidrug resistant gram-negative bacilli in pediatrics

Abstract: The aim of this study was to identify the risk factors for nosocomial bloodstream infections by multidrug resistant Gram-negative bacilli. From November 2001 to December 2003, in the Pediatric Department of the Santa Casa de São Paulo, a retrospective case-control study was developed concerning patients who had nosocomial bloodstream infection caused by Gram-negative bacilli. Patients with multidrug resistant infections were designated as case patients, and control patients were those with an infection that di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
12
1
1
Order By: Relevance
“…It was also the most commonly found infection in this study, though the results contrast with those reported in other studies in which the most frequently occurring infections are bacteremia and pneumonia [1, 23, 25]. …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…It was also the most commonly found infection in this study, though the results contrast with those reported in other studies in which the most frequently occurring infections are bacteremia and pneumonia [1, 23, 25]. …”
Section: Discussioncontrasting
confidence: 99%
“…Different studies have reported the relationship between the hospital environment and the presence of infections caused by resistant bacteria, which has been associated with mortality rates as high as 37 % in the pediatric population [1, 14, 23]. These infections particularly affect children under one year old, a feature that was observed in this study and that can be explained by the immunological immaturity of infancy, which leads to neonatal patients being more susceptible [2326]. …”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Especially in clinics, multidrug-resistant bacteria have become more and more popular among nosocomial infections. 3,26 It is interesting to conduct a case-control study to investigate the prevalence of resistant isolates among healthy community residents and cooks in the community and hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…9 Data from the Sentry antimicrobial surveillance program documented increases in MDR in Latin America, 10 as have other microbiological studies. [11][12][13][14] Few studies have evaluated hospitals in respect to the epidemiology and trends of overall resistance of MDR GNB. 15 Steady increases of different types of phenomena of multidrug resistance are observed in day-to-day practice in our hospital due to the growing complexity of procedures.…”
Section: Introductionmentioning
confidence: 99%